ChemInform Abstract: A Concise Domino Synthesis of Benzo‐1, 4‐heterocycle Compounds via a Piancatelli/C—N Coupling/Michael Addition Process Promoted by La(OTf)3. Issue 18 (11th April 2013) - Liu, Jinqian; Shen, Qiang; Yu, Jianjun; Zhu, Mengyun; Han, Jianwei; Wang, Limin
Abstract This method yields either fused benzoxazines with high diastereoselectivity or fused 1, 2, 3, 4‐tetrahydroquinoxalines as mixtures of diastereomers.